Chinese contemporary art in the global auction market - Archer, Anita (Anita Sarah) (Leiden ; Boston : Brill, 2022)
"Chinese Contemporary Art in the Global Auction Market examines the rapid rise of the global market for Chinese Contemporary art across the turn of the millennium. Focusing on key auction events, it traces the systematic and strategic role played by auction houses in promoting the work of 'avant-garde' Chinese artists, transforming them into multi-million-dollar global art superstars. Anita Archer's research into this emerging art market reveals a powerful global network of collectors, curators, dealers and auction house specialists whose understanding of the mechanics of value formation in the global art world consolidated a framework for the promotion of Chinese Contemporary art to a Western audience"--
Acknowledgements -- List of Illustrations -- 1 Introduction -- 1 Art Auctions, Emerging Markets, and Chinese Contemporary Art -- 2 The Evolution of an Art Auction Market: Christie's, Asian Avant-Garde, 12 October 1998, London -- 1 Introduction -- 2 Auction Market Evolution -- 3 Creating a Platform in the West for Chinese Contemporary Art -- 4 Christie's Asian Avant-Garde, London -- 5 Conclusion -- 3 Joining the Dots to Inaugurate a New Auction Category: Sotheby's Chinese Contemporary Art, 31 October 2004, Hong Kong -- 1 Introduction -- 2 Forming Dots: a Broadening Base of Emerging Market Infrastructure from 1998 to 2004 -- 3 Auction Market Inauguration: Sotheby's Chinese Contemporary Art, Hong Kong -- 4 Conclusion -- 4 Adding Value through Translocation: Sotheby's Contemporary Art Asia, 31 March 2006, New York -- 1 Introduction -- 2 Market Momentum through Consensus Building -- 3 Translocation: Sotheby's Contemporary Art Asia, New York -- 4 Conclusion -- 5 Embedding Chinese Contemporary Art into a Global Market for Art Superstars: Sotheby's Contemporary Art Evening Auction, 12 October 2007, London -- 1 Introduction -- 2 A Global Art Market Boom -- 3 Shaping Superstars: Strategic Responses by the International Auction Houses to the Global Art Market Boom -- 4 Consecrating Contemporary Chinese Art: Sotheby's Contemporary Art Evening Auction, London -- 5 Conclusion -- 6 Investing in, and Profiting from, Symbolic Value in an Emerging Art Market: Sotheby's The Estella Collection, 9 April 2008, Hong Kong -- 1 Introduction -- 2 The Formation of The Estella Collection -- 3 Positioning the Collection for Purpose and Profit -- 4 Conclusion -- 7 Facing Reality and Navigating Global Change: Sotheby's The Ullens Collection, 3 April & 2 October 2011, Hong Kong -- 1 Introduction -- 2 Response and Readjustments after the Global Financial Crash -- 3 The End of a Collector's Dream -- 4 Navigating a Turning Point: Sale of The Ullens Collection -- 5 Conclusion -- 8 Conclusion -- Appendix 1: Summary of Top Hammer Prices Achieved at Auction by Forty-Five Chinese Contemporary Artists, 1998-2020 -- Appendix 2: Auction Results -- Glossary -- Illustration Credit List -- Bibliography.
Revision of the author's thesis (doctoral)--University of Melbourne, 2018, under the title: Global positioning : international auctions and the development of the Western market for Chinese Contemporary art, 1998-2012.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Art auctions -- Western countries; Auction houses -- Western countries; Art, Chinese -- 20th century; Art, Chinese -- 21st century; Art -- Marketing; Art chinois -- 20e siècle.; Art chinois -- 21e siècle.; Art -- Commercialisation; Art -- Vente aux enchères -- Occident; art market; Art auctions; Art, Chinese; Art -- Marketing; Auction houses; Western countries; 1900-2099